Correlation Between Physical Activity and Student Life Satisfaction: A Study on Junior High School Students - Muhammad Labib Siena Ar Rasyid; Himawan Wismanadi; Noortje Anita Kumaat; Afif Rusdiawan; Nisa Hamidah Nur Azizah (Universitas Negeri Surabaya, 2025)
Background: Evidence shows that the level of physical activity of adolescents in the world is still very lacking, while physical activity itself has a holistic effect, both physically and mentally, including on one's life satisfaction. The purpose of this study was to determine the relationship between physical activity and student life satisfaction. Methods: Correlational research was used in this study. A total of 58 students of Jogoroto 1 Junior High School (JHS) consisting of 29 boys and 29 girls. SLSS and IPAQ-SF instruments were used in this study and data analysis techniques used descriptive statistics and Spearman's rho rank correlation test. Results: he correlation test results showed a positive correlation coefficient and significance less than 0.05 between physical activity and student's life satisfaction, both in terms of METs value (r=0.875, p=0.000<0.05) and physical activity category (r=0.929, p=0.000<0.05). Conclusions: There is a significant correlation between physical activity and student's life satisfaction. The higher the level of physical activity, the higher the level of student's life satisfaction.